Odpływ rzek w Polsce w różnych fazach oscylacji północnoatlantyckiej - Wrzesiński, Dariusz (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2010)
Deviations of climatic elements from average levels, like those caused by changes in the atmosphe- ric circulation, modify the conditions in which the river runoff forms. The river regime is controlled by both, precipitation and air temperature, whose magnitudes show a significant dependence on the intensity of zonal circulation. A simple indicator characterising the atmospheric circulation over the north Atlantic is the North Atlantic Oscillation Index (henceforth, NAO). The North Atlantic Oscillation is considered a very important climate-forming factor in Poland. The analysis embraced monthly, seasonal and annual runoff of Polish rivers taking into consideration Hurrell’s winter NAO index from the years 1951–2000. The analysed flow series came from 141 profiles loca- ted on 86 Polish rivers. The selected rivers are distributed evenly throughout Poland and represent a diversity of environmental conditions (Fig. 1). The aim of the present research was to examine the extent to which the North Atlantic Oscillation affects the runoff of Polish rivers: its seasonal structure and spatial variability. Differences were calculated between the monthly, seasonal and annual runoff observed in the years with exceptionally high (NAODJFM > 2) and low (NAODJFM < –2) values of the winter NAO index and their statistical significance was determined. Also calculated were monthly, seasonal and annual deviations of runoff in the years with high NAODJFM indices from that in the years with their low values (assuming the runoff in the years with low NAODJFM indices to be 100%). The research results have confirmed a strong effect of the North Atlantic Oscillation on the runoff volume of the Polish rivers. In the winter months – January, February and March, the most statistically significant positive relations can be observed on rivers in the north-east and north of the country. The river runoff in those regions in a positive NAO stage is then more than 200% higher than in a negative stage. In the spring months, in April hold for ...